THE ASSOCIATION OF HERNIA LUMP COLOUR AND THE PRESENCE OF BOWEL SOUND IN ASSESSING THE VIABILITY OF INCARCERATED INGUINAL HERNIA CONTENTS - M. , Alsen Arlan; R. M. , Ardani Fitriansyah SY; Singh, Sarup; EU Manawan, Efman; M. , Hafidh Komar (International Journal of Psychosocial Rehabilitation, 2020)
Background: The viability of contents in incarcerated inguinal hernia is difficult to assess before operations. According to previous research, there were few significant indicators in order to predict the viability of incarcerated inguinal hernia contents. This study was conducted to investigate whether the incarceration duration, lump color, presence of bowel sound, pain intensity, abdominal distension, and leukocyte values can be used as such indicators. Method: This study was performed using 24 samples involving incarcerated inguinal hernia patients. The data was collected directly from the primary method through a questionnaire, and the responses were analyzed using Spearman bivariate analysis. The analysis was then continued using logistic regression to assess any significant risk factor. Results: In terms of clinical signs, the color of the hernia lump and bowel sound were significant in the bivariate analysis (p=0.000). These 2 risk factors were analyzed using logistic regression and had the same odds ratio of 11.478. Whereas there is no significant association between incarceration duration, pain intensity, abdominal distension, and leukocyte values towards assessing the viability of incarcerated inguinal hernia contents, and thus these risk factors can be dismissed as indicators. Conclusion: Logistic regression analysis showed that the color of the hernia lump and bowel sound can be used to predict the viability of incarcerated inguinal hernia contents preoperatively. Hence, these two variables can be used by health practitioners to properly diagnose the viability of hernia content in medical settings.